A QUALITATIVE CONTENT ANALYSIS OF THE DEVELOPERS’ PERSPECTIVES ON DEVELOPMENT CHARGES - Abdul Rahman, Nor Azalina Yusnita; Mohamed Saraf, Mohamad Haizam; Che Pin, Siti Fairuz; Suratman, Robiah; Samsudin, Salfarina (PLANNING MALAYSIA, 2021)
The conversion of land, increment of plot ratios or density that increases the land value often comes with a development charge. While the local governments view the development charge as one of their income sources for providing utilities to the society, property developers’ communities still contend that the charge surges development uncertainty. Moreover, the existing empirical studies of the implementation of development charges in Malaysia are limited since lack of developers’ views regarding this matter. Through semi structured interviews among the property developers, this paper had explored the property developers’ perspectives on the implementation of development charges in Malaysia. Data from the interviews were analysed using content analysis techniques. Findings from the analysis revealed that the effect it has on property developers seems to have increased the developers’ uncertainties, especially on the cost of property development. This paper provides new insights for future research in the study of relevant approaches to improve the efficiency of the development charge and the effect it has on the developer’s uncertainty.